ANALISIS PERBEDAAN PENGUNGKAPAN INTELLECTUAL CAPITAL BERDASARKAN STRUKTUR KEPEMILIKAN (STUDI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI 2021) - Ahfaz, Mahfuz (Sekolah Tinggi Ilmu Ekonomi Bhakti Pembangunan, 2024)
This research aims to determine the level of disclosure of intellectual capital in each manufacturing company listed on Indonesia Stock Exchange (BEI) in 2021 based on the ownership structure . The variables used in this research are the level of intellectual capital disclosure and ownership structure represented by foreign ownership, managerial ownership, institutional ownership, and family ownership. The sample used consist of 126 manufacturing companies listed on BEI in 2021. The level of intellectual capital disclosure was measured using disclosure score. Data analysis used in this research is Mann-Whitney U Test.. The results of this research indicate that there are differences based on foreign ownership and family ownership. While for managerial ownership and institutional ownership, there were no differences in disclosure of intellectual capital.